HUBUNGAN ANTARA KUALITAS KARAKTER SISWA DENGAN PRESTASI BELAJAR SISWA SMP KECAMATAN HARUAI KABUPATEN TABALONG - Norpah Norpah (JURNAL SOCIUS, 2013)
The focus of this study is the  Haruai junior high school students’ characters quality and their learning achievements.  The students do not show much respect to teachers and others; they are not neat, and they like cheating during exams, etc. Also, they have not good enough in understanding ability. This study aims to describe the students’ characters quality and their learning achievements, and also to find how the characters quality correlate to learning achievements. This study is a survey research using a quantitative method. The research population comprises 316 students of the Haruai junior high school.  The research sample consists of 177 students selected with the multi stage sampling technique.  The data are collected using a Likert’s scale for the students’ characters quality, and a documentation of their learning achievements reports.  The data are analyzed using a correlational technique.The results of the study show that: (1) the Haruai junior high school students’ characters quality is weak.  (2) the Haruai junior high school students’ learning achievements is bad. (3) there is a significant correlation of the Haruai junior high school students’character quality and their learning achievement.  It is expected that the social studies teachers and other teachers in general build better learning process and implement character education.Key words: Character education, Character quality, and learning achievement